IMPROVING THE FINANCIAL RESOURCES OF FARMS - Nosirov, Bahodirjon; Abdurashidov , Akbarali (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The purpose of this article is to focus on the financial sustainability of the farms in Uzbekistan by using and managing the financial resources effectively. Today, the agricultural and livestock farms in Uzbekistan are not only producing agricultural products but also storing, processing and packaging agricultural and livestock products as well as supplying and meeting the needs of consumers in the rural areas. It is important to note that providing services also contributes to the economic stability of the country. One of the challenges facing the current situation of agricultural and livestock farms is to create an optimal quantity of current assets